2005 International Conference on Computer Design
DOI: 10.1109/iccd.2005.89
|View full text |Cite
|
Sign up to set email alerts
|

Quick scan chain diagnosis using signal profiling

Abstract: In this paper we address the scan chain diagnosis problem. We propose a new diagnosis flow based on the concept of signal profiling to accurately pinpoint the location of a faulty flip-flop in a scan chain. As compared to the conventional cause-effect or effect-cause analysis, this approach is much more computationally efficient because it does not have to simulate the behaviors of a large number of fault candidates. Also, it is general and applicable to all kinds of faults because it does not assume any speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The highest score indicates the most possible fault position. Most recent works on software-based scan chain diagnosis belong to simulation-based solutions [2,[7][8][9][10][11]. Scan cell fault candidates can be identified even by using conventional ATPG patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The highest score indicates the most possible fault position. Most recent works on software-based scan chain diagnosis belong to simulation-based solutions [2,[7][8][9][10][11]. Scan cell fault candidates can be identified even by using conventional ATPG patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Recent large industrial design [1] reported that nearly 44% of transistors in the logic part of the design reside within scan cells. In addition, it is reported that almost 50% defects can cause scan chain failure [2]. Therefore, defects are prone to impact both scan chains and system logic.…”
Section: Introductionmentioning
confidence: 99%